Balance Remains Impaired after Hip Arthroplasty: A Systematic Review and Best Evidence Synthesis - Giorgio Di Laura Frattura; Vittorio Bordoni; Pietro Feltri; Augusto Fusco; Christian Candrian; Giuseppe Filardo (Diagnostics, 2022)
Background: Hip arthroplasty (HA) is the most common intervention for joint replacement, but there is no consensus in the literature on the real influence of this procedure on balance, or on what factors in the pre-operative, surgical, and post-operative stages may affect it. Purpose: To synthesize the evidence on how Hip Arthroplasty (HA) affects balance, identifying pre-operative, surgical, and postoperative risk factors that may impair balance in HA patients, with the aim to improve patients’ management strategies. Methods: A literature search was performed on PubMed, PeDRO, and Cochrane Collaboration on 25 May 2021. Inclusion criteria: clinical report of any level of evidence; written in English; with no time limitation; about balance changes in hip osteoarthritis (OA) patients undergoing HA and related factors. Results: 27 papers (391 patients) were included. Overall, the evidence suggested that balance is impaired immediately after surgery and, 4–12 months after surgery, it becomes better than preoperatively, although without reaching the level of healthy subjects. A strong level of evidence was found for hip resurfacing resulting in better balance restoration than total HA (THA), and for strength and ROM exercises after surgery positively influencing balance. Conclusion: Both the surgical technique and the post-operative protocols are key factors influencing balance; thus, they should be carefully evaluated when managing hip OA in patients undergoing HA. Moreover, balance at 4–12 months after surgery is better than preoperatively, although without reaching the level of the healthy population. Attention should be paid in the early post-operative phase, when balance may be impaired in patients undergoing HA.